Bromatological composition and in situ ruminal degradability of agroindustrial residues of passion fruit (Passiflora edulis) and banana (Musa paradisiaca) - Espinoza Guerra, Italo (2017)
The objective of the study was to evaluate the in situ ruminal degradability of the dry, organic and inorganic matter of passion fruit peel residues, passion fruit seeds and banana peel, from the food and juice processing industry. Representative samples were taken to determine the chemical composition and the in situ degradability technique was used at 0, 3, 6, 12, 24, 48 and 72 hours of ruminal incubation. The passion fruit peel and seed, presented higher values of organic matter (89.46-97.21%), protein (16.56-14.55%), ash (10.54-10.70%), neutral detergent fiber (70.75-63.24%), lower fiber content acid detergent (30.73-37.45%) and crude fat (2.98-4.91%), in relation to the passion fruit seed that showed lower values of organic matter, crude protein, ash, acid detergent fractions (89.30, 8.16 and 38.87%), and higher values of crude fat and neutral detergent fiber (9.60 and 70.75%). In the in situ degradability of the dry matter and organic matter the banana peel had the highest (p